Exosome α-Synuclein Release in Plasma May be Associated With Postoperative Delirium in Hip Fracture Patients - Yuan, Yi; Li, Zhengqian; Yang, Ning; Han, Yongzheng; Ji, Xiaojuan; Han, Dengyang; Wang, Xiaoxiao; Li, Yue; Liu, Taotao; Yuan, Feng; He, Jindan; Liu, Yajie; et al. (Frontiers in Aging Neuroscience, 2020)
Background: Little is known about the underlying mechanisms of the similarities in the core features of postoperative delirium (POD) and α-synuclein (α-syn)-related cognitive disorders. We herein investigated associations between fluctuated levels of exosomal α-syn in the plasma and POD presentation in geriatric hip fracture patients. Methods: We conducted an observational, prospective, and 1:1 matched (on age older than 65, hip fracture diagnosis, American Society of Anesthesiologist’ (ASA) physical status, duration of surgery, and intraoperative bleeding) case-control study: POD cases and non-POD controls were selected from the overall cohort by using Confusion Assessment Method (CAM). Delirium severity was measured by the Memorial Delirium Assessment Scale (MDAS). Plasma exosome levels of α-syn were examined preoperatively and at the time that POD was diagnosed, by using an established immunocapture technology based on a putative brain-cell-specific marker. Circulating concentrations of interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) were also determined. The relationship between α-syn levels and POD risk, as well as the association between α-syn and MDAS scores and plasma cytokines, were assessed. Results: POD incidence was 8.4% (17/202). Postoperative α-syn were either elevated or lowered. As primary outcome variables, the change of α-syn in POD patients was significantly higher than non-POD ones (21.0 ± 29.3 pg.ml−1 vs.1.9 ± 20.0, P = 0.047). The α-syn alteration was positively correlated to MDAS (r = 0.436, P = 0.010) and the change of IL-6 (r = 0.383, P = 0.025). Conclusions: Exosome α-syn release in plasma may be associated with the POD development which might be due to systemic inflammation. Clinical Trial Registration: www.clinicaltrials.gov, identifier ChiCTR-IPR-17012301. Prior Presentation: The abstract of this work has been selected for presentation in the 2019 ANESTHESIOLOGY Journal Symposium “What’s New with the old,” and it has been present in the ASA 2019 annual meeting October 21st, 2019 in Florida.